(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Political implication and policy implementations of most of the governmental bodies have brought unprecedented damages to the population around the world. The rise of private corporations affects the lifestyle of people. Culture of any country has undergone a drastic change over the years due to the mutual involvement of the politicians and the capitalists. The sustainability of many countries is at the brink of a downfall due to selfish attitude and carelessness of the people. Noam Chomsky, in his Who Rules the World highlights the misgivings of social and political constructs with which people live in and that pave way for political problems. Critics of Cultural Poetics consider a literary work as something based on a specific cultural context and developed with various social and cultural factors. They attempt to discover the original ideology behind the creation of the work. Politicians and large conglomerates work together to attain prominence, power and profit. This paper proposes to examine Chomsky’s perspective of the political power exercised by the United States of America having manipulated by corporate elites.